Amorphous/crystalline silicon heterojunction solar cells via remote inductively coupled plasma processing - Xu, L. X. (2013)
Low-frequency inductively coupled plasma (ICP) has been widely used to deposit amorphous or microcrystalline Si thin films, but the intrinsic drawback namely ion bombardment effect limits its application in Si heterojunction solar cells. In this letter, we redesigned typical ICP and realized a remote plasma deposition with suppressed ion bombardment effect. This remote ICP system enables the synthesis of high quality amorphous Si layers with a compact network and a high hydrogen content (10.5%). By using this remote ICP system, we achieved amorphous/crystalline silicon heterojunction solar cells with an efficiency of 14.1% without any back surface field or textures.